STUDI LABORATORIUM PENGARUH TEMPERATUR TERHADAP PROPERTIES LUMPUR KCL POLYMER - Yohanes, Yandri; Afifah, Rohima Sera; Risna, Risna; Amiruddin, Amiruddin (PETROGAS: Journal of Energy and Technology, 2025)
This study investigates the effect of temperature on the properties of KCl polymer-based drilling mud, focusing on maintaining the stability of these properties under varying temperature conditions. Five sample variations were tested: Sample A at room temperature, Sample B1 at 150°F, Sample B2 at 200°F, Sample B3 at 250°F, and Sample C at 250°F with the addition of selected additives. The B series samples showed a decline in mud quality as temperature increased, with Sample B3 falling outside the required specification limits for plastic viscosity, yield point, gel strength, and API filtrate due to high-temperature effects. To address this, additives were introduced in Sample C to enhance the composition and stabilize the mud properties. As a result, Sample C met the required specifications with plastic viscosity of 14 lbs/100ft², yield point of 32 lbs/100ft², gel strength of 9 lbs/100ft² after 10 seconds and 12 lbs/100ft² after 10 minutes, and API filtrate of 5.2 cc/30 minutes. The mud properties must be maintained to prevent hole problems in the formation during drilling operationsKeywords : Mud Fluid, Mud Properties, Tempreature